EVALUASI DOKUMEN ASPEK TEKNIS PADA PROSES PELELANGAN KONTRAKTOR DENGAN APILKASI METODE AHP (ANALYTICAL HIERARCHY PROCESS) - M.Agung Wibowo; Heri Suliantoro; Shinta Marithyanti (TEKNIK, 2011)
The procurement process could be defined as all the activities required in getting a product or a service from thesupplier to the customer. It consists of the purchasing function, storing, transportation and managers therelations between suppliers and internal customers. The Analytical Hierarchy Process (AHP) is acomprehensive, logical structured frame work. It allows to improve understanding of complex decission systemby decomposing the problems. The AHP is based three principles which are decomposition of the problems,comparative judgement of the elements and synthesis of the priorities.The objectives of this study are to identify criteria involved in the contractor bidding process, to elaboratetechnical aspect involeved in the bidding process based on committee’ experince and to discuss and to comparethe outputs obtained based on the committee’ experience and the application of the AHP.The results of the study said that construction method has the highest ranking compare other apecst which is27%. The next ranking are time scheduling (16%), technical specification and material (13%), organizationalproject and person incharged (10%), construction labour scheduling (10%), list of equipment (8%), cash flowestimation (6%), list of sub-contractor and project site facilities (5%). These rangking could be used todetermine the score of contractors to do bidding process.